Community indicators and collective impact: facilitating change. Issue 2 (14th March 2016) - Wood, Danielle M.
Abstract: This article provides insights into facilitating collective impact with community indicator programs (CIPs). The research deconstructs effective programs in two communities and explores the role of community indicators and institutional design in facilitating change. A CIP analytical framework drawn from relevant literature provides a model to assist in analyzing the structure and processes around the CIPs of the Alliance for Building Community (Quincy, IL) and the Jacksonville Community Council (Jacksonville, FL). Next, using process-tracing methods, this research follows a successful community initiative and its local systems approach. These observations, along with the relevant broader findings from the literature, provide revisions to the analytical framework and generalizable processes and factors in developing such a system.